The Institutionalization of Community Mediation for Resolving Merarik Marriage Disputes in Sasak Community - Hilman Syahrial Haq; Nasri Nasri; Khudzaifah Dimyati; Absori Absori (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2019)
Mediation is applicable for various disputes within the society, including family dispute. Such a method is commonly referred to as community mediation. This paper discusses the application of community mediation for resolving merarik marriage dispute in Sasak Community, Lombok. This socio-legal research conducted through both library-based study and field work. Interview and non-participatory observation have been conducted in several locations including Sesait Village, Mambalan Village and Rambitan Village. It is found that community mediation should be institutionalized in order to improve its effectiveness. The institutionalization of community mediation can be made by integrating it into the national justice system. It is expected that community mediation can be an alternative mechanism to the court system especially in handling merarik marriage disputes.